2010
DOI: 10.1021/ar900193h
|View full text |Cite
|
Sign up to set email alerts
|

New Methodologies for the Conservation of Cultural Heritage: Micellar Solutions, Microemulsions, and Hydroxide Nanoparticles

Abstract: Modern civilization's inherited artworks have a powerful impact on society, from political, sociological, and anthropological points of view, so the conservation of our Cultural Heritage is fundamental for conveying to future generations our culture, traditions, and ways of thinking and behaving. In the conservation of cultural artifacts, scientists intervene in the degradation of often unique handcrafts, resulting from a delicate balance of aging, unpredicted events, environmental conditions, and sometimes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
144
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

5
4

Authors

Journals

citations
Cited by 180 publications
(147 citation statements)
references
References 32 publications
0
144
0
3
Order By: Relevance
“…A previously formulated nanofluid, based on ethyl acetate and propylene carbonate [17][18][19], was combined with a poly(2-hydroxyethyl methacrylate (pHEMA)/ poly(vinylpyrrolidone) (PVP) semi-interpenetrated polymer network (sIPN) [16,20,21] and used to selectively remove a white acrylic modern paint from a white acrylic paint laid on a mortar sample. Cleaning results were, then, characterized by means of visual and photographic observation, optical microscopy, and FT-IR microreflectance investigation.…”
Section: Introductionmentioning
confidence: 99%
“…A previously formulated nanofluid, based on ethyl acetate and propylene carbonate [17][18][19], was combined with a poly(2-hydroxyethyl methacrylate (pHEMA)/ poly(vinylpyrrolidone) (PVP) semi-interpenetrated polymer network (sIPN) [16,20,21] and used to selectively remove a white acrylic modern paint from a white acrylic paint laid on a mortar sample. Cleaning results were, then, characterized by means of visual and photographic observation, optical microscopy, and FT-IR microreflectance investigation.…”
Section: Introductionmentioning
confidence: 99%
“…), and their low solvent content reduces the environmental impact. In fact, throughout the last decade, nanostructured fluids have been widely tested for the cleaning of mural paintings, and the results obtained have demonstrated that these systems are a valid alternative to the use of neat solvents [8][9][10][11]. However, for their use on watersensitive substrates, o/w microemulsions must be confined within a retentive network that allows their controlled release, so as to grant the removal of unwanted layers without excessive wetting of the surface.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the pictorial surface of the work of art can be disrupted (see Fig. 2.3) in a period of time ranging roughly from less than 10 to 50 years, the degradation being enhanced by fluctuations of temperature and relative humidity, and by pollution (Giorgi et al 2010a). For instance, the combination of the presence of a Mowilith film (vinyl acetate/acrylate copolymer) and salt crystallization produced in less than 10 years the irreversible loss of portions of original wall paintings in the archaeological site of Mayapan (Mexico, Post-Classic Age 1200-1450 BC), and degradation of paintings (e.g.…”
Section: Introductionmentioning
confidence: 99%